Innovation development strategy for hybrid learning based English teaching and learning - Entis Sutisna; Lungguh Halira Vonti (University of Kuningan, 2020)
This research is motivated by the importance of the modernization of the implementation of learning in the education system within the university. The existence of various limitations of human resources, study space, and time to face-to-face causes the learning process to experience various obstacles to achieve optimal results. Learning in the form of Hybrid learning is one of several alternative efforts to improve the quality and quantity of the lecture process. Through learning by using Hybrid learning, students and lecturers can interact in learning across distances, time and space. The objective of this research was to obtain an overview of the Hybrid learning model to improve digital literacy of students in the learning process. The data obtained from this study were the results of document analysis, observation, interviews, and questionnaires. The sources of this study were students of the English Language Study Program, Faculty of Teacher Training and Educational Sciences, Pakuan University who were registered as active students for the 2018/2019 school year. The stages of research were observation, instrument calibration, research, evaluation, data analysis, revision of research results, dissemination of results, and reporting. The result of the research showed that the students' digital literacy was improved through the process of hybrid learning.